The epidemiology of proximal femur fractures during COVID-19 emergency in Italy: a multicentric study - Ciatti, Corrado; Maniscalco, Pietro; Quattrini, Fabrizio; Gattoni, Serena; Magro, Alessandra; Capelli, Patrizio; Banchini, Filippo; Fiazza, Caterina; Pavone, Vito; Puma Pagliarello, Calogero; Valenti, Fabiana; Maccauro, Giulio; et al. (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: After the first Italian case of Covid-19, the Government imposed the complete closure of all areas involved by the spread of the virus to contain transmissions. There was a massive reorganization of Hospitals, a stop of all elective activities and a convertion of many hospitals in “Covid Centers’’. AITOG (Associazione Italiana Traumatologia e Ortopedia Geriatrica) conducted a retrospective study on all proximal femur fractures surgeries that occurred in this period, to find out whether the pandemic and the correlated lockdown somehow changed the incidence of these events. Methods: 10 Italian orthopedic centers were involved in the study. Considering the geographic location, three groups were created (North, Centre and South). The considered period is the Italian “Phase 1” (February 23rd - May 3rd 2020). Results: the cohort is composed of 412 patients, 116 male and 296 female (mean age 81.1 ± 9.1 years). The same period of 2019 has been used as control group, with 558 patients, 156 male and 402 female (mean age 84.2 ± 8.0 years). In 2020 we counted 323 (78.4%) fractures occurred at home, 61 (14.8%) in retirement houses and 28 (6.8%) in different locations. We mainly treated fractures with intramedullary nails (n.237 57.5%). Among all patients we had 46 (11.1%) Covid-19 positive. The mortality rate within 30 days was of 51 patients (12.4%); 23 of these died because of complications related to Covid-19 while 31 of these were in treatment with anticoagulant/antiaggregant. Conclusions: AITOG analysis demonstrates a decrease in surgical interventions for proximal femur fractures from 2019 to 2020, a reduction in patients mean age and an increase in trauma occurred in domestic environment. We also registered a consistent difference between the North, Center and South of the Country.